El papel de la radio en la preservación de la música y cultura tradicional en el Ecuador - Almeida Acosta, Nathaly Michelle (2025)
This thesis analyzes the role of radio in the preservation of traditional music and culture in Ecuador, highlighting its importance as an accessible medium to transmit values and cultural identity, especially in rural contexts. Despite its relevance, radio currently faces significant challenges in terms of globalization, digitization and also the decrease in interest of young audiences, the results reflect the existence of a reduction in the programming of traditional cultural content that is attributed to changes in legislation and also the lack of innovative strategies. There is a very high demand for the presence of traditional cultural content on the radio. It is recommended to develop strategies where the interest in traditional culture can be revitalized, encourage alliances with educational institutions for the creation of cultural content projects.